Preparation method of lithium manganese iron phosphate composite material

The fast ion conductor cladding layer is generated in situ by the liquid phase method to solve the challenges of lithium manganese iron phosphate positive electrode materials in terms of cycle stability and charge and discharge performance, and achieve high cycle stability and high capacity lithium manganese iron phosphate composite materials, which are suitable for industrial applications.

CN119797309APending Publication Date: 2025-04-11CHANGZHOU LIYUAN NEW ENERGY TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510016210.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Lithium manganese iron phosphate (LiMnFePO4) cathode materials have challenges in cyclic stability and charge and discharge performance, especially due to the conductivity difference and Jahn-Teller effect caused by the introduction of manganese ions, which affect their cyclic stability.

Method used

The fast ion conductor cladding layer is generated in situ by the liquid phase method to solve the problem of coating uniformity. The appropriate lithium-phosphorus ratio and reaction temperature are used to control the amount of Li3PO4 in the reaction system to achieve uniform cladding of lithium manganese iron phosphate composite material.

Benefits of technology

The cycle stability and charge and discharge performance of lithium manganese iron phosphate composite materials are improved, the cycle stability is higher than 92%, the actual specific capacity is >140mAh/g, and the gentleness of the reaction conditions is reduced, making it suitable for industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797309A_ABST
    Figure CN119797309A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a lithium manganese iron phosphate composite material, which comprises the following steps: (1) preparing a first mixture containing Li < + >, PO4 < 3-> and water, with the ratio of Li to P in the first mixture being 2.5-4: 1 based on the amount of element substance, and maintaining the temperature of the first mixture at 85-105 DEG C; (2) preparing a second mixture containing Mn < 2 + >, Fe < 2 + > and water, adding the second mixture into the first mixture to obtain a reactant, reacting for not less than 4 hours, taking a solid in the reactant to obtain a lithium manganese iron phosphate precursor, in the reactant, (Mn + Fe): P = 1: (1-1.1), and pH = 6-8.5; and (3) mixing the lithium manganese iron phosphate precursor, a composite carbon source and doped metal, sanding, drying and calcining to obtain the lithium manganese iron phosphate composite material. According to the preparation method, a proper amount of unconverted Li3PO4 exists in a reaction system, the fast ion conductor is coated in situ by a liquid phase method, and the capacity and the cycling stability are both considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for synthesizing an electrode material, and in particular to a method for preparing a lithium manganese iron phosphate composite material. Background Art

[0002] As a new type of positive electrode material for lithium-ion batteries, lithium manganese iron phosphate (LiMnFePO4) has attracted widespread attention due to its high energy density, good thermal stability and safety. It combines the high safety of lithium iron phosphate (LFP) and the high voltage characteristics of lithium manganese phosphate (LMP), and has a higher theoretical energy density than LFP. However, due to the introduction of manganese ions, it has the disadvantage of poor conductivity. At the same time, its Jahn-Teller effect is obvious, resulting in poor cycle stability. These are the two major problems that lithium manganese iron phosphate (LMFP) positive electrodes have to face.

[0003] In order to solve the problem of poor conductivity, the existing modification schemes are mainly divided into three categories: coating, morphology control, and ion doping. Among them, ion conductor coating is a branch of carbon coating, and LiAlO2, Li3VO4, Li2SiO3, Li3PO4 and other materials with high electronic conductivity, ionic conductivity and Li + The conductive material with high storage capacity is coated to provide a fast channel for the transfer of electrons / ions during the charging and discharging process of the material, thereby improving the conductive properties of the material (Wen Zhipeng, Pan Kai, Wei Yi, et al. Research Progress on Modification of Lithium Iron Manganese Phosphate Cathode Material [J]. Energy Storage Science and Technology: 1-18), and the ion conductor coating is mostly carried out by solvothermal method or solid phase method, such as the invention patent application with publication number CN 118561259 A discloses a spherical lithium iron manganese phosphate cathode material and its preparation method, application and lithium battery: first prepare the iron manganese phosphate cathode material, then mix the spherical lithium iron manganese phosphate cathode material with carbon source and fast ion conductor lithium titanium aluminum phosphate to obtain a spherical lithium iron manganese phosphate cathode material coated with carbon and fast ion conductor, and improve the electronic conductivity and ion conductivity of the lithium iron manganese phosphate cathode material. However, the conductive material introduced by the coating method depends on the solubility of the conductive material, and there is a problem of uneven coating. The in-situ generation of the liquid phase method can effectively solve this problem, but an excessively thick fast ion conductor layer is likely to lead to a decrease in the capacity of the LMFP. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a lithium iron manganese phosphate composite material, which solves the problem of uniformity of the coating layer by a liquid phase method, so that the lithium iron manganese phosphate composite material has both cycle stability and charge and discharge performance.

[0005] Technical solution: The method for preparing a lithium iron manganese phosphate composite material of the present invention comprises the following steps:

[0006] (1) Configuration containing Li + PO4 3- A first mixture, wherein Li:P in the first mixture is 2.5 to 4:1 in terms of the amount of elemental substances, and the temperature of the first mixture is maintained at 85 to 105° C.;

[0007] (2) Configuration containing Mn 2+ , Fe 2+ The second mixture is added to the first mixture to obtain a reactant, and the reaction is carried out for not less than 4 hours. The reactant solid is taken to obtain a lithium manganese iron phosphate precursor, wherein the reactant has (Mn+Fe):PO4=1:1-1.1, and pH=6-8.5;

[0008] (3) Mixing a lithium iron manganese phosphate precursor, a composite carbon source, and a doped metal, sand grinding, drying, and calcining to obtain a lithium iron manganese phosphate composite material.

[0009] Preferably, in step (1), the temperature of the first mixture is maintained at 95-105°C.

[0010] Preferably, in step (1), Li + From one or more of lithium carbonate, lithium hydroxide and lithium dihydrogen phosphate; PO4 3- Derived from one or more of phosphoric acid, ammonium dihydrogen phosphate and lithium dihydrogen phosphate.

[0011] Preferably, in step (2), the second mixture contains: Mn:Fe=1.5-1.6:1.

[0012] Preferably, in step (2), among the reactants, PO4 3- The concentration is 0.3~0.45mol·L -1 Excess PO4 3- It will change the proportion of each element in the reaction system in disguise, resulting in an imbalance in the overall proportion of the product and a significant reduction in purity.

[0013] Preferably, in step (2), Mn 2+ From one or more of manganese sulfate, manganese carbonate and manganese iron oxide; Fe 2 + Derived from a mixture of one or more of ferrous chloride, ferrous sulfate and ferrous oxalate.

[0014] Preferably, in step (3), the pH of the reactants is 6 to 7. Weakly acidic conditions are helpful in increasing the capacity.

[0015] Preferably, in step (3), the drying is carried out by spray drying, the inlet temperature of the spray drying is 250-280°C, the outlet temperature is between 80-100°C, and the median particle size D of the product obtained by spray drying is 50 20~30μm.

[0016] Preferably, in step (3), the calcination conditions are: in an inert atmosphere, sintering at 660-720° C. for 8-12 hours.

[0017] Preferably, in step (3), during sand grinding, the solid content is controlled to be 35-40%.

[0018] Preferably, in step (3), based on the mass of the lithium iron manganese phosphate precursor, the addition ratio of the composite carbon source is 8% to 12%; and the addition ratio of the doping metal is 2000 to 3000 ppm.

[0019] Preferably, in step (3), the calcination conditions are: sintering at 660-720° C. for 8-12 hours in an inert atmosphere.

[0020] Preferably, in step (3), based on the mass of the lithium iron manganese phosphate precursor, the addition ratio of the composite carbon source is 8% to 12%; and the addition ratio of the doping metal is 2000 to 3000 ppm.

[0021] Preferably, the carbon source includes an organic carbon source and a high molecular polymer, and the ratio of organic carbon source to high molecular polymer is 6 to 7:4 to 3 by mass. The organic carbon source is a mixture of one or more of glucose, sucrose, citric acid and urea, the high molecular polymer is one or more of polyethylene, polypropylene and polyvinyl pyrrolidone, and the doped metal is a mixture of one or more of oxides or salts of titanium, magnesium, aluminum and vanadium.

[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: 1. The lithium manganese iron phosphate composite material takes into account both cycle stability and charge-discharge performance: by controlling the lithium-phosphorus ratio and the reaction temperature, an appropriate amount of unconverted Li3PO4 is present in the reaction system, thereby achieving in-situ coating, and the resulting LMFP cycle stability is higher than 92%, and the actual specific capacity is greater than 140 mAh / g; 2. The reaction conditions are stable: no hydrothermal method or solvent thermal method is required, the temperature is reduced, the reaction conditions are milder, and it is suitable for industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the XRD pattern of LMFP prepared in Example 3 of the present invention;

[0024] Figure 2 This is a SEM image of LMFP precursor A prepared in Example 1 of the present invention;

[0025] Figure 3 This is a SEM image of LMFP precursor A prepared in Example 2 of the present invention;

[0026] Figure 4This is a SEM image of LMFP precursor A prepared in Example 3 of the present invention;

[0027] Figure 5 This is a SEM image of the LMFP prepared in Example 3 of the present invention; DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0029] Example 1: Synthesis of lithium iron manganese phosphate

[0030] (1) Mix 12 mol Li2CO3, 8 mol H3PO4 and 19 L deionized water (the molar ratio of Li:P is 3:1), ensure that the pH is 8 after mixing evenly, and then heat to 95°C.

[0031] (2) Mix 4.8 mol MnSO4·H2O, 3.2 mol FeSO4·7H2O and 5 L deionized water, add the corresponding mass of concentrated sulfuric acid to adjust the pH after all are dissolved, and after the temperature in step (1) reaches 95°C, use a peristaltic pump to slowly pump it into step (1), and maintain the pump speed at 2-2.5 L / h. Start timing after all are pumped in, react for 4 hours, and ensure that the initial reaction system pH is 7.8-8.2. After the reaction is completed, filter and take the solid, wash the solid with deionized water three times and ethanol three times, and then put it in a 100°C oven for 12 hours to obtain LMFP precursor A.

[0032] (3) Precursor A is mixed with glucose, polyvinyl pyrrolidone and titanium dioxide, and deionized water is added to mix and stir. The solid content is maintained at 35%. After mixing evenly, the mixture is poured into a sand mill for sand grinding. The amount of glucose added is 7% of the total mass of phosphoric acid, the amount of polyvinyl pyrrolidone added is 1.5% of the total mass of phosphoric acid, and the titanium dioxide is maintained at 2500ppm.

[0033] (4) The sand-milled slurry was spray-dried, with the inlet temperature maintained at 280°C, the outlet temperature maintained at 85-90°C, and the D50 maintained at 28-30 μm, to obtain LMFP precursor B.

[0034] (5) The LMFP precursor B was calcined in a nitrogen atmosphere at a temperature of 700°C for 10 h to obtain a LMFP positive electrode material doubly coated with a fast ion conductor Li3PO4 and carbon.

[0035] Example 2: Synthesis of lithium iron manganese phosphate

[0036] (1) Mix 12 mol Li2CO3, 8 mol H3PO4 and 15 L of ionized water (the molar ratio of Li:P is 3:1), ensure that the pH is 8 after mixing evenly, and then heat to 95°C.

[0037] (2) Mix 4.8 mol MnSO4·H2O, 3.2 mol FeSO4·7H2O and 5 L deionized water, and add the corresponding mass of concentrated sulfuric acid to adjust the pH after all are dissolved. After the temperature in step (1) reaches 95°C, use a peristaltic pump to slowly pump it into step (1), and maintain the pump speed at 2-2.5 L / h. Start timing after all are pumped in, and react for 4 hours to ensure that the initial reaction system pH is 7-7.5. After the reaction is completed, filter and take the solid. Wash the solid three times with deionized water and three times with ethanol. After washing, put it in a 100°C oven for 12 hours to obtain LMFP precursor A.

[0038] (3) Precursor A is mixed with sucrose, polyvinyl pyrrolidone and magnesium oxide, and deionized water is added to mix and stir, and the solid content is maintained at 40%. After mixing evenly, pour into a sand mill for sand grinding. The amount of sucrose added is 7% of the total mass of phosphoric acid, the amount of polyvinyl pyrrolidone added is 1.5% of the total mass of phosphoric acid, and the magnesium oxide is maintained at 2500ppm.

[0039] (4) The sand-milled slurry was spray-dried, with the inlet temperature maintained at 280°C, the outlet temperature maintained at 85-90°C, and the D50 maintained at 28-30 μm, to obtain LMFP precursor B.

[0040] (5) The LMFP precursor B was calcined in a nitrogen atmosphere at a temperature of 700°C for 10 h to obtain a LMFP positive electrode material doubly coated with a fast ion conductor Li3PO4 and carbon.

[0041] Example 3: Synthesis of lithium iron manganese phosphate

[0042] (1) Mix 12 mol Li2CO3, 8 mol H3PO4 and about 19 L of deionized water (the molar ratio of Li:P is 3:1), ensure that the pH is 8 after mixing evenly, and then heat to 95°C.

[0043] (2) Mix 4.8 mol MnSO4·H2O, FeSO4·7H2O and 5 L deionized water, add the corresponding mass of concentrated sulfuric acid to adjust the pH after all are dissolved, and after the temperature in step (1) reaches 95°C, use a peristaltic pump to slowly pump it into step (1), and maintain the pump speed at 2-2.5 L / h. Start timing after all are pumped in, react for 4 hours, and ensure that the initial reaction system pH is 6-6.5. After the reaction is completed, take the solid, wash the solid with deionized water three times, and with ethanol three times, and then put it in a 100°C oven for 12 hours to obtain LMFP precursor A.

[0044] (3) Precursor A is mixed with sucrose, polyvinyl pyrrolidone and magnesium oxide, and deionized water is added to mix and stir, and the solid content is maintained at 40%. After mixing evenly, pour into a sand mill for sand grinding. The amount of sucrose added is 7% of the total mass of phosphoric acid, the amount of polyvinyl pyrrolidone added is 1.5% of the total mass of phosphoric acid, and the magnesium oxide is maintained at 2500ppm.

[0045] (4) The sand-milled slurry was spray-dried, with the inlet temperature maintained at 280°C, the outlet temperature maintained at 85-90°C, and the D50 maintained at 28-30 μm, to obtain LMFP precursor B.

[0046] (5) The LMFP precursor B was calcined in a nitrogen atmosphere at a temperature of 700°C for 10 h to obtain a LMFP positive electrode material doubly coated with a fast ion conductor Li3PO4 and carbon.

[0047] Example 4: The synthesis steps (1) to (5) of this example are the same as those of Example 3, except that the amount of Li2CO3 added is 16 mol.

[0048] Comparative Example 1: This comparative example is similar to Example 1, except that in step (1) and step (2), the reaction temperature is 80°C.

[0049] Comparative Example 2: This comparative example is similar to Example 1, except that in step (1), the amount of Li2CO3 added is 4 mol.

[0050] Comparative Example 3: This comparative example is similar to Example 1, except that in step (1), the amount of Li2CO3 added is 8 mol.

[0051] Comparative Example 4: In this comparative example, lithium iron manganese phosphate is synthesized, and the operation steps are as follows:

[0052] (1) Mix 12 mol Li2CO3, 8 mol H3PO4 and corresponding 19 L deionized water (the molar ratio of Li:P is 3:1), ensure that the pH is 8 after mixing evenly, and then heat to 120°C.

[0053] (2) Mix 4.8 mol MnSO4·H2O, FeSO4·7H2O and 5 L deionized water, and add the corresponding mass of concentrated sulfuric acid to adjust the pH after all are dissolved. After the temperature in step (1) reaches 120°C, use a peristaltic pump to slowly pump it into step (1), and maintain the pump speed at 2-2.5 L / h. Start timing after all are pumped in, and react for no less than 4 hours to ensure that the initial reaction system pH is 6-6.5. After the reaction is completed, filter out the solid, wash the solid with deionized water three times, and with ethanol three times, and then put it in a 100°C oven for 12 hours to obtain LMFP precursor A.

[0054] (3) Precursor A is mixed with sucrose, polyvinyl pyrrolidone, magnesium oxide, and lithium phosphate, and deionized water is added to mix and stir, and the solid content is maintained at 40%. After mixing evenly, pour into a sand mill for sand grinding. The amount of sucrose added is 7% of the total mass of phosphoric acid, the amount of polyvinyl pyrrolidone added is 1.5% of the total mass of phosphoric acid, the amount of magnesium oxide is maintained at 2500ppm, and the amount of lithium phosphate added is 0.15mol. Steps (4) and (5) are the same as in Example 3.

[0055] Performance test: The samples prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were subjected to charge and discharge tests. The test results are shown in Table 1 below.

[0056] Table 1: Charge and discharge data

[0057]

[0058] In the above table, LiMnFePO4 and Li3PO4 were obtained from the final product XRD data through jade fitting, which are semi-quantitative data.

[0059] Under high temperature conditions, the lithium phosphate layer in LMFP will decrease (Phys.Chem.Chem.Phys., 2015, 17, 18629). In order to make the lithium phosphate layer content in comparative example 4 similar to that in Example 3, lithium phosphate was coated on the surface of the precursor A in comparative example 4 to form a lithium phosphate coating layer. The test results show that the LMFP in comparative example 4 has high purity and guaranteed capacity, but the cycle stability is less than 90%. The reason may be that the solubility of lithium phosphate is poor and it is impossible to form a uniform coating layer. The in-situ generation of fast ion conductors can not only obtain a uniform coating layer but also improve the cycle stability performance. In comparative example 1, the temperature was reduced to 80°C, and more lithium phosphate layers were generated, but the cycle stability decreased. The reason may be that there was too much lithium phosphate, and the elements of the product obtained at this temperature were unbalanced, affecting the overall purity of the product; in comparative examples 2 and 3, the lithium-phosphorus ratio was reduced, the lithium phosphate layer was reduced, and the cycle stability was promoted. The reason may be that there were too few lithium phosphate layers and a continuous layer could not be formed, but the overall electrical performance decreased significantly, indicating that the addition ratio of this element could not form a product with higher purity.

[0060] In Examples 1 to 3, the cycle stability of the obtained products is greatly improved. Compared with Examples 1 and 2, in Example 3, the pH of the reaction system is weakly acidic, and the capacity is further improved, indicating that adjusting the pH helps to further increase the capacity; in Example 4, the lithium-phosphorus ratio is further increased, and the obtained product LMFP takes into account both capacity and stability, but the performance is slightly lower than that of Example 3, which is similar to the phenomenon in Comparative Example 1, indicating that the lithium phosphate layer should not be further increased, otherwise it will have a negative effect.

Claims

1. A method for preparing a lithium manganese iron phosphate composite material, characterized in that: The following steps are involved: (1) Configuration containing Li + PO4 3- , water, wherein Li:P in the first mixture is 2.5 to 4:1 based on the amount of elemental substances, and the temperature of the first mixture is maintained at 85 to 105° C.; (2) Configuration containing Mn 2+ , Fe 2+ , and a second mixture of water, adding the second mixture to the first mixture to obtain a reactant, reacting for not less than 4 hours, taking a solid from the reactant to obtain a lithium manganese iron phosphate precursor, wherein the reactant has (Mn+Fe): P=1:1-1.1, and pH=6-8.5; (3) Mixing a lithium iron manganese phosphate precursor, a carbon source, and a doping metal, sand grinding, drying, and calcining to obtain a lithium iron manganese phosphate composite material.

2. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: In step (1), the temperature of the first mixture is maintained at 95-105°C.

3. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: In step (2), among the reactants, PO4 3- The concentration is 0.3~0.45mol·L -1 .

4. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: In step (2), the pH of the reactant is adjusted by concentrated sulfuric acid, and the pH of the reactant is 6-7.

5. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: In step (3), the drying is carried out by spray drying, the inlet temperature of the spray drying is 250-280°C, the outlet temperature is 80-100°C, and the median particle size D of the product obtained by spray drying is 50 20~30μm.

6. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: In step (3), the calcination conditions are: sintering at 660-720° C. for 8-12 hours in an inert atmosphere.

7. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: In step (3), based on the mass of the lithium iron manganese phosphate precursor, the addition ratio of the composite carbon source is 8% to 12%; the addition ratio of the doping metal is 2000 to 3000 ppm.

8. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: The carbon source includes an organic carbon source and a high molecular polymer. By mass, the ratio of organic carbon source to high molecular polymer is 6 to 7:4 to 3. The organic carbon source is a mixture of one or more of glucose, sucrose, citric acid and urea. The high molecular polymer is one or more of polyethylene, polypropylene and polyvinyl pyrrolidone. The doped metal is a mixture of one or more of oxides or salts of titanium, magnesium, aluminum and vanadium.

9. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: In step (1), Li + From one or more of lithium carbonate, lithium hydroxide and lithium dihydrogen phosphate; PO4 3- Derived from one or more of phosphoric acid, ammonium dihydrogen phosphate and lithium dihydrogen phosphate.

10. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: In step (2), Mn 2+ From one or more of manganese sulfate, manganese carbonate and manganese iron oxide; Fe 2+ Derived from a mixture of one or more of ferrous chloride, ferrous sulfate and ferrous oxalate.

Citation Information

Patent Citations

  • Spherical lithium iron manganese phosphate positive electrode material, preparation method and application thereof, and lithium battery

    CN118561259A